2023
DOI: 10.1101/gad.350906.123
|View full text |Cite
|
Sign up to set email alerts
|

Target-directed microRNA degradation regulates developmental microRNA expression and embryonic growth in mammals

Abstract: MicroRNAs (miRNAs) are post-transcriptional regulators of gene expression that play critical roles in development and disease. Target-directed miRNA degradation (TDMD), a pathway in which miRNAs that bind to specialized targets with extensive complementarity are rapidly decayed, has emerged as a potent mechanism of controlling miRNA levels. Nevertheless, the biological role and scope of miRNA regulation by TDMD in mammals remains poorly understood. To address these questions, we generated mice with constitutiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 59 publications
3
24
0
Order By: Relevance
“…The suppression of TDMD stabilizes multiple miRNAs in variable tissues and cell cultures (Shi et al 2023;Jones et al 2023;Han et al 2020;Shi et al 2020). Similarly, we revealed the repertoire of miRNAs repressed with the involvement of Dora in OSCs, including miR-7-5p (Figure 2B,C).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The suppression of TDMD stabilizes multiple miRNAs in variable tissues and cell cultures (Shi et al 2023;Jones et al 2023;Han et al 2020;Shi et al 2020). Similarly, we revealed the repertoire of miRNAs repressed with the involvement of Dora in OSCs, including miR-7-5p (Figure 2B,C).…”
Section: Discussionsupporting
confidence: 76%
“…This likely indicates that some TDMD targets exist for both miR-10 strands. It was shown that the destabilization of one of the miRNA strands by TDMD may facilitate its antisense counterpart to be dominantly loaded and preserved in the complex with Ago and thus may be the mechanism of regulating 'arm switching' (Shi et al 2023;Jones et al 2023). The control of stability of mature miRNAs and, related to this, the determination of active strands by degradation of their counterparts allow TDMD to affect the content of cellular miRNA pool.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar studies were conducted back-to-back, again by the Bartel and Mendell groups, detailing ZSWIM8 lossof-function during mouse development (Jones et al, 2023;Shi et al, 2023). Each group independently reached the same conclusion, that ZSWIM8 loss-of-function mice displayed low birth weight, cyanosis, and significantly underdeveloped cardiopulmonary systems, resulting in perinatal lethality (Jones et al, 2023;Shi et al, 2023). Given the tissue-specific alterations observed, and the potential for tissue-specific expression of miRNAs and triggers alike, detailed examination of altered miRNA abundance was conducted in a variety of mouse tissues.…”
Section: Mus Musculusmentioning
confidence: 71%